ANALYSE DE L’EFFICACITE OFFENSIVE DES EQUIPES NATIONALES DE FOOTBALL: CAS DE LA COUPE D’AFRIQUE DES NATIONS - Ekou, Nuama (European Scientific Journal, ESJ, 2012)
The objective of this paper is to study the evolution of the sportive performance of participant countries to the African Nations football Cup during the edition 2004, 2006, 2008 et 2012 with a stochastic frontier. The study shows that participant countries are besides of the efficiency frontier; their average sportive performance is about 73%. Moreover, their productive efficiency decreases about 2% during the edition. The decreasing of sportive performance score is synonym of the decreasing general level of this competition and this must award the authorities the African Confederation of football on the future of this competition.